MICROSPHERULES OF ALUMINOSILICATE GLASS IN GOLD ORES - Novgorodova M.I.; Agakhanov A.A.; Dikaya T.V.; Gamyanin G.N.; Zhdanov Yu.Ya. (My University, 2003)
Microspherules of aluminosilicate glass are found and studied in ores of the Nezhdaninskoe and Kellyam (Yakutia), Democrat (Alaska), and Kokpatas (Uzbekistan) gold-quartz and gold-quartz-sulfide deposits. They show a great diversity of major element concentrations and contain glass inclusions of contrasting composition. The microspherules are believed to form by microexplosion cavitation phenomena in fluxes of boiling and unmixing hydrothermal solutions.